2015
DOI: 10.1021/jacs.5b05457
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Bridged Terthiophene Dimers: How Sulfur Oxidation State Controls Interchromophore Electronic Coupling

Abstract: Symmetric dimers have the potential to optimize energy transfer and charge separation in optoelectronic devices. In this paper, a combination of optical spectroscopy (steady-state and time-resolved) and electronic structure theory is used to analyze the photophysics of sulfur-bridged terthiophene dimers. This class of dimers has the unique feature that the interchromophore (intradimer) electronic coupling can be modified by varying the oxidation state of the bridging sulfur from sulfide (S), to sulfoxide (SO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 76 publications
2
45
0
Order By: Relevance
“…This trend can be attributed to the electronic screening by the sulfur electron lone-pairs, which limits the interactions between the two sets of π-electrons, as recently discussed in sulfur-bridged terthiophene dimers. 10 On the other hand, the LE/CT B couplings are much larger in the sulfide than in the sulfoxide bridge in accordance with the amount of CT B in the excitation, which can be rationalized as a result of the presence of one additional electron lone-pair in the former.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This trend can be attributed to the electronic screening by the sulfur electron lone-pairs, which limits the interactions between the two sets of π-electrons, as recently discussed in sulfur-bridged terthiophene dimers. 10 On the other hand, the LE/CT B couplings are much larger in the sulfide than in the sulfoxide bridge in accordance with the amount of CT B in the excitation, which can be rationalized as a result of the presence of one additional electron lone-pair in the former.…”
Section: Resultsmentioning
confidence: 96%
“… 9 This trend was later scrutinized in the case of terthiophene dimers. 10 The study concluded that rapid intersystem crossing (ISC) to the triplet state manifold is the main deactivation process limiting the fluorescence quantum yield, as observed in pristine terthiophene. 11 , 12 The ISC efficiency is reduced in the presence of intramolecular charge transfer (CT), which can be tuned by the oxidation state of the bridging sulfur group.…”
Section: Introductionmentioning
confidence: 99%
“…From these results, the degree of electronic coupling follows the order (PDI) 2 > p ‐(PDI) 2 ≈ m ‐(PDI) 2 . To further examine the origins of the Davydov splitting, the relative energy differences Δ E in the transition band were theoretically calculated according to a reported method . The detailed calculation processes are shown in the Supporting Information, Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…From these results, the degree of electronic coupling follows the order (PDI) 2 > p-(PDI) 2 % m-(PDI) 2 .T of urther examinet he origins of the Davydovs plitting, the relative energy differences DE in the transition band were theoretically calculated according to ar eportedm ethod. [23] The detailed calculation processes are shown in the Supporting Information, Ta ble S3. Briefly,t he DE values weree stimated to be (PDI) 2 :1 9cm À1 , p-(PDI) 2 : 16 cm À1 ,a nd m-(PDI) 2 :3 .1 cm À1 .H owever,u nfortunately these estimated values are unreliable because of underestimation of DE is due to the large contribution of the charge-transfer state.…”
Section: Steady-state Absorption Spectramentioning
confidence: 99%
“…Our group has shown that varying the oxidation state at sulfur can have pronounced effects on the electronic properties of organic chromophores 42,43 and luminescent inorganic complexes. [44][45][46] In this study, the synthesis and optoelectronic characterization of a series of six new heteroleptic Cu(I) species utilizing sulfur-bridged dipyridyl ligands in either the sulfide 4 (II) or sulfone (VI) oxidation state as the N^N component, and bis [2-(diphenylphosphino)phenyl]ether (DPEPhos) as the P^P component are discussed.…”
Section: Introductionmentioning
confidence: 99%